The Role of Biosecurity in the Control of Campylobacter: A Qualitative Study of the Attitudes and Perceptions of UK Broiler Farm Workers - Royden, Alexandra; Christley, Robert; Prendiville, Alison; Williams, Nicola J. (Frontiers in Veterinary Science, 2021)
Campylobacter is the leading cause of human bacterial diarrhoeal disease worldwide, with poultry meat products contributing to a large proportion of cases. Due to the ubiquitous presence of Campylobacter in the poultry farm environment, biosecurity is the main area for intervention to prevent colonisation of commercial broiler chicken flocks. However, research has repeatedly demonstrated that farmers' uptake of biosecurity recommendations is often poor. This study explored farmers' attitudes towards biosecurity and identified barriers to effective implementation of biosecurity protocols. Semi-structured interviews were conducted with 1–3 members of staff on each of 16 broiler farms; 6 owned by, and 10 contracted to, 3 different UK poultry integrators. In total, 28 interviewees participated, including farm owners, managers, and workers, with a range of industry experience. Thematic analysis of the interviews revealed high levels of recognition amongst broiler farmers of the importance of Campylobacter and the responsibility of the whole farm-to-fork chain within the poultry industry to reduce Campylobacter contamination of chicken meat for the benefit of public health. Participants' self-reported awareness and implementation of biosecurity has improved significantly following the industry-wide focus on Campylobacter control. However, there are frustrations with the industry's approach to tackling Campylobacter and the heavy burden of responsibility that has been put on interventions at the farm-level. There was also scepticism amongst participants as to the effectiveness of current biosecurity measures in the reduction of Campylobacter. Nevertheless, the interviewees' recognition of the benefit of improved biosecurity on broiler health and welfare and other important targets, such as reducing antimicrobial usage, leaves a legacy of which the UK broiler industry can be proud. There is scope for further farmer education about the evidence supporting biosecurity interventions, particularly in the control of Campylobacter, and a need to establish more effective channels of communication. Furthermore, to give all players within the industry agency and investment in industry targets, contributions from all levels should be permitted in the design of future biosecurity interventions. Biosecurity compliance may be improved through collaborative efforts, such as participatory and co-design practises, to facilitate knowledge co-creation and exchange.